(untitled) (Commonwealth Journal of Local Governance, 2021)
Against a backdrop of strikingly limited research on the subject, this article examines citizens’ trust in upazila parishads (UzPs) – a historically significant form of local government institution (LGI) in Bangladesh. A set of indicators has been developed that help to evaluate citizens’ trust in these LGIs. Alongside secondary literature and official document reviews, a mixed-method approach was adopted for empirical data collection combining quantitative (a questionnaire targeting a cross-section of service recipients) and qualitative ( key informant interviews with LGI service providers) methods. The results revealed a poor level of citizen trust in UzPs, as the majority of respondents expressed dissatisfaction with their performance. This low level of citizens’ trust was attributable to such reasons as delays in service delivery, dishonest and unfair practices, and disrespectful treatment by service providers. From a ‘supply-side’ perspective, service providers mentioned many constraints to good performance including the challenge of meeting growing demand with inadequate resources, frequent staff transfers, limited scope for training on modern technologies, and pressure and interference from influential elites.